(untitled) (Journal of actual problems of jurisprudence, 2018)
Article is devoted to the political and legal views of the famous statesman during the Jungar invasion Buhar zhyrau. Fighting Dzungar invasion opened the development of ideas of national unity, the concentration of power. Considering that the policy of the neighboring countries in the face of China and Russia threatening the country’s independence, he saw the foundation to ensure the independence in unity and stability. Zhyrau sees the solution to the problems of his era to strengthen traditional values and finding strength within themselves. Key words: monarchism, the concentration of power, freedom, the will, independence, unity.